Analysis and modeling of client order flow in limit order markets. Issue 2 (1st February 2023) - Cont, Rama; Cucuringu, Mihai; Glukhov, Vacslav; Prenzel, Felix
Abstract : Four distinct clusters of client order flow are identified and their properties analyzed